Strategic Management in Multinational Enterprises: A Literature Analysis - Hamdat, Aminuddin; B, Ceskakusumadewi; Samalam, Abdul Gafar; Susanto, Setya Ega; Rizal, Muhammad (Vifada Management and Digital Business, 2024)
This study examines entry mode strategies within multinational enterprises (MNEs) through a comprehensive literature analysis, aiming to elucidate the dynamic nature of the global business landscape and its implications for strategic management. Utilizing a blend of quantitative and qualitative methodologies alongside theoretical frameworks such as transaction cost economics and the eclectic paradigm, the research explores factors influencing entry mode selection and execution across diverse international markets. Findings highlight the critical role of strategic agility and adaptability in effectively navigating regulatory environments, cultural nuances, and competitive dynamics. Strategic alliances, partnerships, and collaborative networks emerge as pivotal mechanisms for MNEs to harness external resources, mitigate risks, and capitalize on emerging opportunities. Moreover, digital technologies are increasingly vital in facilitating seamless coordination and customization of entry-mode strategies, empowering MNEs to respond swiftly to evolving market conditions. The study underscores the importance of aligning entry mode strategies with organizational objectives and market dynamics, emphasizing the need for MNEs to balance global integration with local responsiveness. Practical implications include guidance for managerial decision-making, reinforcing the notion that adaptability and strategic alignment are pivotal in sustaining competitive advantage in diverse global markets.